1989
DOI: 10.1021/la00085a019
|View full text |Cite
|
Sign up to set email alerts
|

Formation of multilayers by self-assembly

Abstract: Monolayer and multilayer films were formed by self-assembly of methyl 23-(trichlorosilyl)tricosanoate (1) from organic solution. In agreement with published results, this compound was found to form good quality, close-packed monolayers on silicon surfaces. We have, however, found that films significantly thicker than the three monolayers previously obtained can be formed from continued chemisorption of monolayers of this compound followed by reduction of the surface ester with LiAlH4 in THF to form an "alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
198
0
4

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(214 citation statements)
references
References 6 publications
12
198
0
4
Order By: Relevance
“…pSi-RC(O)NHS). Very high yields for the activation reaction were found for a restricted range of NHS and EDC concentrations and molar ratios (5 …”
Section: Formation and Derivatization Of Carboxylic Acid-based Monolamentioning
confidence: 96%
See 1 more Smart Citation
“…pSi-RC(O)NHS). Very high yields for the activation reaction were found for a restricted range of NHS and EDC concentrations and molar ratios (5 …”
Section: Formation and Derivatization Of Carboxylic Acid-based Monolamentioning
confidence: 96%
“…Namely, there was an inhomogeneous in-plane distribution of surface active sites and poorly defined polymerised material among the reaction products. 5 Further, the silicon-oxygen bonds that are formed tend to be prone to hydrolysis, especially under basic conditions, and thermal degradation of the structure has been reported. 6 Despite their intrinsic limitations, silane layers (Si-O-SiR) gave researchers a novel tool to modify surfaces with unprecedented control.…”
Section: Jason B Harpermentioning
confidence: 99%
“…While only two or three layers could be grown before structural defects in the film became important, this work laid the conceptual foundation for later, more successful systems. Tillman et al recently used an analogous technique in which the terminal group was a protected carboxylic acid rather than an olefin (33 an ordered multilayer film which adopts the well-known Zr(03PR)~ structure (Fig. 4) is produced (34).…”
Section: Chemistw2mentioning
confidence: 99%
“…Maoz and Sagiv [99] also found that high concentrations lead to disordered monolayers. Surprisingly, some scientists did not hesitate to put a few drops of water in their silane solution prior to the deposition [100]. As a consequence, Ulman et al [100,101] had to scrub their samples with detergent and a soft camel hairbrush to remove gel aggregates.…”
Section: Growth and Structure Of Siloxane Samsmentioning
confidence: 99%
“…Surprisingly, some scientists did not hesitate to put a few drops of water in their silane solution prior to the deposition [100]. As a consequence, Ulman et al [100,101] had to scrub their samples with detergent and a soft camel hairbrush to remove gel aggregates. The water in the solvent is in equilibrium with the surface water from the substrate [102].…”
Section: Growth and Structure Of Siloxane Samsmentioning
confidence: 99%